ri Kajian Camilan Tortilla Chips dari Formulasi Tepung Jagung dan Tempe untuk Pencegahan Stunting: Study of Tortilla Chips Snack from Corn Flour and Tempeh Formulation for Stunting Prevention - Reni Indriyani; Yulia Novika; Mindo Lupiana; Endang Sri Wahyuni (Universitas Airlangga, 2023)
Background: Nutritional problems during pregnancy can affect the health of the mother and fetus. Stunting is a chronic malnutrition that must be addressed immediately. One of the food products that can be given to pregnant women and children under five with high nutritional value, especially protein, and calcium content, is tortilla chips. Objectives: Analyzing the formula of tempeh with corn flour in tortilla chips to increase protein value and calcium content. Methods: This study used an experimental study of adding tempeh and corn flour to tortilla chips. A randomized block design with five formulas for adding tempeh F1=0%, F2=10%, F3=20%, F4=30%, and F5=50%, with five replications was done. Observations included organoleptic assessment and laboratory analysis. The data analysis used the parametric type ANOVA test with a value of α=0.05 with a follow-up BNT test. Results: F2 was the best formulation regarding color (3.69) and assessment of sensory parameters (3.71). F3 is the best formulation based on aroma (3.72) and taste (3.72) organoleptic tests. F5 was the highest organoleptic test for texture (4.05), protein, and calcium content. The most preferred addition of tempeh to tortilla chips is the 10% formulation. The ANOVA test showed significant differences in the organoleptic test for color (0.001), texture (0.02), aroma (0.001), taste (0.001), overall sensory parameter assessment (0.001), protein (0.001), and calcium (0.02). Conclusions: There was a significant difference in the average organoleptic assessment of color (F2=3.69), texture (F3=3.61), aroma (F3=3.72), taste (F3=3.94), and preference rating of various tortilla chip formulations with the best tortilla chip formula on F2.